Rational Expectations, Information Signalling and Dividend Adjustment to Permanent Earnings - Kao, Chihwa; Wu, Chunchi (The Review of Economics and Statistics, 1994)
The authors propose a rational signaling model to investgate the information content of dividends. The model provides a direct test of the relation between unexpected dividend and earnings changes. In identifying the component of unexpected dividend changes, the authors suggest an expectations framework that accounts for the process of dividend adjustment to firms' permanent earnings. A nonlinear regression method is used to estimate the model and test the rationality and signaling hypotheses. Consistent with Paul Healy and Krishna Palepu's (1988) findings, the results show that dividends reflect past, current, and future earnings information. Copyright 1994 by MIT Press.